Perencanaan Aplikasi Lamella Separator di Kota Kupang - Oktavina G. LP Manulangga (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Population growth can cause a decrease in water quality in raw water sources due to human activities and land use around the source. Water that can be consumed must meet the Regulation of the Minister of Health of the Republic of Indonesia No.492/MENKES/PER/IV/2010, which includes physical, chemical and biological requirements. One of the chemical parameters in water quality requirements is the amount of calcium (ca) and magnesium (mg) in the water, the presence of which is known as water hardness. The maximum level of hardness that is allowed in drinking water according to the Minister of Health of the Republic of Indonesia Number 492/MENKES/PER/IV/2010 is 500 mg/liter. The source of raw water used by PDAM Kupang City comes from ground water and surface water. Based on chemical examination of water samples, Namosain spring has a high level of hardness, namely 606 mg/L CaCO3 compared to other springs. Lamella Separator is a sedimentation technology for purifying and recycling water and separating particles and turbidity from dirty water. Based on the author's previous research, the lamella separator was able to reduce the hardness up to 89.287%. So that the lamella separator can be used as an alternative treatment to reduce hardness on a household scale in Kupang City. The lamella separator application is planned to serve residents in Kupang City with a population of Kupang City in 2021 as many as 455.847 people with the assumption of kk 5 people so that the time required to treat 1497.64 L of water per day is 1.1 hours and the volume of the reservoir designed must be able to accommodate the volume of water of 15,000 m3.